Surviving the Wreck: Post-traumatic Writers, Bodies in Transition and the Point of Autobiographical Fiction. Issue 4 (1st October 2016) - Jensen, Meg
ABSTRACT: In autobiographical fiction, the repetition of specific 'unprocessed' tropes wherein contextual meaning remains unclear can be likened to the symptomatic 'flashbacks' endured by victims of trauma. Virginia Woolf's compulsive use of images of sea, mirrors, and unspoken shame, Jack Kerouac's brothers and angels, J. G. Ballard's empty swimming pools, Melville's tropes of Narcissus and madness and my own return to images of blood and wounding in my work, are part of each writer's attempt to construct a new post-trauma narrative identity. Writing fiction enabled these writers to shake off the fixed subject position dictated by their pasts and construct new and more multifaceted identity narratives as survivor- writers. As Maggie Schauer's work demonstrates, through narrativisation a new 'sense of perceived identity may emerge: 'who I am now' and 'who I was' when trauma struck. These narratives comprise the past as a story written post-traumatically, and a new identity (as a survivor/writer) they have narrated for themselves. Autobiographical fiction, therefore, may be central to understanding the function of self-narrative in the construction of post-trauma identities. This essay considers what such texts can tell us about trauma and the body, trauma narratives and autobiographical fictions, and writing and post-traumatic identity.